Estimation and comparison of thrombocyte count by peripheral blood smear method and automated method in women with pregnancy - Chaturvedi, Vineet; Mabood, Abdul; Gupta, Shalini; Gupta, Shivani; K. S., Kiran; Agarwal, Savita; Pandey, Pinki (International Journal of Research in Medical Sciences, 2019)
Background: Thrombocyte is important and very essential component of blood and have significant role in maintenance of hemostasis. Thrombocyte count is an important investigation done in various acquired and congenital coagulable states which include conditions like pregnancy. Thrombocyte count is routinely done by automated hematology analyzer method. The automated hematology analyzer counters are not usually available at all centres especially in peripheral and rural side though thrombocytes can also be assessed from the peripheral blood smears, which can be easily and precisely done at any set up. Aim and objective of this study was to compare the thrombocyte estimation by peripheral blood smear method and automated hematology analyzer in pregnant women. Methods: Thrombocyte estimation was done from samples taken from 120 normal pregnant women between December 2018 to March 2019, where samples were Ethylene Diamine Tetra Acetic acid (EDTA) anticoagulated. Thrombocyte was counted manually using PBS (Leishman stain) and hematology analyzer (Sysmex XN1000 series). Thrombocyte counts were expressed in Mean and standard Deviation. Statistical analysis was done by student’s t test using MS excel and SPSS version 17. Results: Thrombocyte count by PBS have mean value of 2.04 lacs/mm3 with standard deviation of 0.56 lacs/mm3 and by automated method have mean value of 1.89 lacs/mm3 and standard deviation of 0.71 lacs/mm3 with p value 0.010. Thus, there was no statistically significant difference found between two methods. Conclusions: Estimation of thrombocyte count on the basis of manual thrombocyte count is a reliable technique and can be used to validate automated thrombocyte counts. It can also be used in under resourced laboratories, where there are no automated counters of good precision available. In fact, all the tests showing abnormal thrombocyte counts must be reported only after cross examining on PBS.